Hydrogen Gas Production from Chip Magnesium Waste and Investigation of Rate Profiles - Oz, Cisem; Coskuner Filiz, Bilge; Kanturk Figen, Aysel (GAZI UNIV, 2018)
In recent years, researches about the use of hydrogen (H-2) as a high-potential energy carrier and replacement with current systems have been enhanced. Production of H-2 with zero emission, safe storage, efficient distribution and, highly efficient energy conversion in end-use are the most important factors for popularizing the use of hydrogen energy systems in daily life. The main target is to develop alternative techniques to produced hydrogen with zero emission instead of fossil-based sources. In particular, magnesium (Mg) from light weight metals has been gain attention to achieve this target. While, Mg and Mg alloys are mainly used as a raw material in automotive, space engineering, metallurgy and chemistry sectors, cells and cathodic protection, % 50 of raw Mg is formed as a waste. However, only 33% of these wastes are classified based on waste managent and reused is being possible. In this research article, the evaluation of the industrial waste grade Mg chips in the production of H-2 gas is studied. H-2 production is carried out based on the hydrolysis reaction and it is necessary to use an activator which accelerates the passage of H+ ions and chlorine salts, metals and acids are preferred for this purpose. The usage of different concentrations of vinegar solutions (0.8-4 % wt. acetic acid, CH3COOH) as an activator in hydrolyses meduim was investigated. Hydrogen prodcution was carried our from waste Mg chip and H-2 gas production profiles were illuminated.
Keywords: H-2 production; waste magnesium; hydrolysis; vinegar; HYDROLYSIS REACTION; FUEL-CELLS; GENERATION; SEAWATER; WATER; NI; COMPOSITE; HYDRIDES; ACID; Engineering